Characterization of the Etna volcanic emissions through an active biomonitoring technique (moss-bags): Part 1 – Major and trace element composition. (January 2015) - Calabrese, S.; D'Alessandro, W.; Bellomo, S.; Brusca, L.; Martin, R.S.; Saiano, F.; Parello, F.
Highlights: First study of volcanic emissions by using moss-bags. The concentration of trace metals in mosses increased significantly after exposure. High levels of toxic trace elements were found in summit and downwind areas of Etna. Tl was the most enriched element in exposed moss-bags with respect to the moss blank. Enrichment factors highlighted the main volcanic and geogenic sources of particles. Abstract: Active biomonitoring using moss-bags was applied to an active volcanic environment for the first time. Bioaccumulation originating from atmospheric deposition was evaluated by exposing mixtures of washed and air-dried mosses ( Sphagnum species) at 24 sites on Mt. Etna volcano (Italy). Concentrations of major and a large suite of trace elements were analysed by inductively coupled mass and optical spectrometry (ICP-MS and ICP-OES) after total acid digestion. Of the 49 elements analysed those which closely reflect summit volcanic emissions were S, Tl, Bi, Se, Cd, As, Cu, B, Na, Fe, Al. Enrichment factors and cluster analysis allowed clear distinction between volcanogenic, geogenic and anthropogenic inputs that affect the local atmospheric deposition. This study demonstrates that active biomonitoring with moss-bags is a suitable and robust technique for implementing inexpensive monitoring in scarcely accessible and harsh volcanic environments, giving time-averaged quantitative results of the local exposure to volcanic emissions. This task is especially important in the study area because the summit area of Mt. Etna is visited by nearly one hundred thousand tourists each year who are exposed to potentially harmful volcanic emissions.